MENJINAKKAN ALGORITMA DI PESANTREN MELALUI EKSPLORASI FENOMENOLOGIS KESIAPAN TECHNOSTRESS TENAGA KEPENDIDIKAN DALAM INTEGRASI AI - Nur Annisa Almaidah (Jurnal Manajemen Pendidikan, 2026)
Objective: The rapid advancement of Artificial Intelligence (AI) has significantly transformed the management of educational institutions, including Islamic boarding schools (pesantren). AI integration provides opportunities to improve administrative efficiency, academic services, and data-driven decision-making. However, its implementation may also generate technostress, a psychological strain caused by the need to adapt to new technologies. This study aims to explore the readiness of educational staff in pesantren for AI implementation using a phenomenological approach. The research focuses on participants' lived experiences in understanding AI, the forms of technostress they encounter, the factors influencing their readiness, and the adaptive strategies they develop. Data were collected through in-depth interviews, observations, and documentation, and analyzed using phenomenological analysis. The findings indicate that readiness for AI implementation is influenced not only by technological infrastructure but also by digital competence, leadership support, organizational culture, and psychological preparedness. These findings highlight that successful AI integration in pesantren requires a human-centered approach that prioritizes capacity building and psychological well-being, enabling AI to serve as a tool for empowerment rather than a source of stress.